Interactions of the Immune System with Human Kidney Organoids - Anusha S. Shankar; Hector Tejeda-Mora; Zhaoyu Du; Quincy Nlandu; Virginia Palomares-Cabeza; Thierry P. P. van den Bosch; Sander S. Korevaar; Fabiany Da Costa Gonçalves; Eric M. J. Bindels; R. Kramann; R. Kramann; R. Kramann; et al. (Transplant International, 2024)
Kidney organoids are an innovative tool in transplantation research. The aim of the present study was to investigate whether kidney organoids are susceptible for allo-immune attack and whether they can be used as a model to study allo-immunity in kidney transplantation. Human induced pluripotent stem cell-derived kidney organoids were co-cultured with human peripheral blood mononuclear cells (PBMC), which resulted in invasion of allogeneic T-cells around nephron structures and macrophages in the stromal cell compartment of the organoids. This process was associated with the induction of fibrosis. Subcutaneous implantation of kidney organoids in immune-deficient mice followed by adoptive transfer of human PBMC led to the invasion of diverse T-cell subsets. Single cell transcriptomic analysis revealed that stromal cells in the organoids upregulated expression of immune response genes upon immune cell invasion. Moreover, immune regulatory PD-L1 protein was elevated in epithelial cells while genes related to nephron differentiation and function were downregulated. This study characterized the interaction between immune cells and kidney organoids, which will advance the use of kidney organoids for transplantation research.